Prevalence of Salmonella Spp. Bacteria Antibiotic Resistance in Digestion Tract in the Broiler Farms of Subang District - Septa Walyani; Trioso Purnawarman; Etih Sudarnika (Faculty of Animal Science, Universitas Gadjah Mada, 2019)
This study is aimed to estimate the prevalence of resistant Salmonella spp., determine the spread of bacterial resistance and investigate the serotypes of bacteria in the chicken’s digestion tract in the broiler farms in Subang District. As many as 74 farms were chosen, five poled caeca samples were taken from each farm and tested for isolation and identification of Salmonella spp. Salmonella isolates obtained were tested antimicrobial susceptibility against 8 antibiotics using the agar dilution method. The antibiotics were gentamycin, tetracycline, ciprofloxacin, nalidixic acid, ampicillin, chloramphenicol, trimethoprim, and sulfamethoxazole. The result showed that 8 out of 74 samples were positive for Salmonella. The prevalence of Salmonella spp. in the digestion tract was 10.8%; 95% confidence interval 3.7%-17.9%. Based on the serological test eight serotypes obtained were Salmonella enteritidis, Salmonella oslo, Salmonella narashino, Salmonella nakuru, and Salmonella nordufer. The result of antibiotic resistance test showed that from 8 Salmonella isolates obtained, 12.5% were found to be sensitive, 75% isolates were resistant to one or two antibiotics, and the remaining 12.5% isolates were resistant to more than two antibiotics; 95% confidence interval (0%-35.4%). The prevalence of resistant Salmonella spp. bacteria in chicken digestion tract in broiler farms in Subang District was high, so integrated control program to reduce antimicrobial resistance problem in broiler farm are greatly needed.